Human Psychophysiology Is Influenced by Low-Level Magnetic Fields: Solar Activity as the Cause - Hanzelka, Michael; Dan, Jiří; Fiala, Pavel; Dohnal, Přemysl (MDPI, 2021)
We evaluate the impact of changes in solar activity on three significant human psychophysiological parameters: skin conductance, electromyography (EMG), and the share of abdominal and diaphragmatic breathing in overall ventilation. Variations affecting human psychophysiology due to changes in solar activity directly document the assertion that psychology, behavior, and decision-making all reflect geomagnetic field alterations that stem from variable solar activity. The relevant experiments showed that solar processes, during which the Earth is exposed to electrically charged particles from the Sun (solar wind), exert an impact on the psychophysiological parameters of the body.

We evaluate the impact of changes in solar activity on three significant human psychophysiological parameters: skin conductance, electromyography (EMG), and the share of abdominal and diaphragmatic breathing in overall ventilation. Variations affecting human psychophysiology due to changes in solar activity directly document the assertion that psychology, behavior, and decision-making all reflect geomagnetic field alterations that stem from variable solar activity. The relevant experiments showed that solar processes, during which the Earth is exposed to electrically charged particles from the Sun (solar wind), exert an impact on the psychophysiological parameters of the body.
Human Psychophysiology Is Influenced by Low-Level Magnetic Fields: Solar Activity as the Cause
Keywords: BioGraph Infiniti; skin resistance; abdominal; diaphragmatic breathing; EMG; BioGraph Infiniti; skin resistance; abdominal; diaphragmatic breathing; EMG